2021
DOI: 10.1007/s42729-021-00459-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of phoD-Harbouring Bacterial Community Structure and Its Roles in Phosphorus Transformation in Steppe Soils in Northern China

Abstract: The phoD-harbouring bacterial community is responsible for much of the hydrolysis of organic phosphorus (P o ) in soils and is therefore significant for the improvement of soil phosphorus (P) availability. However, the distribution of phoD-harbouring bacterial community structure and how it regulates the soil P fractions in steppe soils remain largely unknown. It is necessary to assess these relationships to maintain sustainable development on the steppe. We sampled soils from three steppe types across Inner M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These suggested that Cupriavidus, Pseudomonas, Streptomyces and Xanthomonas can be used as powerful species to mineralize soil organic phosphorus. In consistent with us, Gou et al (2021) noted that Amycolatopsis, Pseudomonas and Streptomyces were positively correlated with soil available P. Similarly, Zhu et al (2021) found that the relative abundances of Bradyrhizobium were positively correlated with labile-Po, suggesting that these bacteria possessed strong ability to mineralize organic P and promote organic P transformation (Godwin and Cotner 2015). We must acknowledge that, in some sense, the linkage between functional microorganisms, phosphatase activity and Po transformation is still a challenge, even though culture-independent approach in this study rapidly screened out the potential species in driving Po mineralization.…”
Section: Linkage Between Po Fractions and Phod Communitysupporting
confidence: 76%
“…These suggested that Cupriavidus, Pseudomonas, Streptomyces and Xanthomonas can be used as powerful species to mineralize soil organic phosphorus. In consistent with us, Gou et al (2021) noted that Amycolatopsis, Pseudomonas and Streptomyces were positively correlated with soil available P. Similarly, Zhu et al (2021) found that the relative abundances of Bradyrhizobium were positively correlated with labile-Po, suggesting that these bacteria possessed strong ability to mineralize organic P and promote organic P transformation (Godwin and Cotner 2015). We must acknowledge that, in some sense, the linkage between functional microorganisms, phosphatase activity and Po transformation is still a challenge, even though culture-independent approach in this study rapidly screened out the potential species in driving Po mineralization.…”
Section: Linkage Between Po Fractions and Phod Communitysupporting
confidence: 76%
“…3b and d). As previously demonstrated, Bradyrhizobium has the ability to promote the conversion of non-labile P to labile P forms through microbial immobilization and subsequent mineralization (Luo et al, 2017;Ibny et al, 2019;Zhu et al, 2021). Additionally, Bradyrhizobium harbors a N-fixing gene (Kaneko et al, 2002;Yao et al, 2014), suggesting that this genus could play an important role in coupled N/P cycling in soils with sufficient C. However, this was not observed in G10-rhizosphere soil (Fig.…”
Section: Phod Harboring Bacterial and Fungal Community Response To Labile C Additionmentioning
confidence: 61%
“…Specifically, we found that Bradyrhizobium is one of the major genus from Proteobacteria in this study (relative abundance range of 22.69–11.36% along low-elevation to high-elevation gradient). Previous study showed that Bradyrhizobium harbors phoD gene in steppe soil, which attributed to microbial immobilization by promoting the conversion of the non-labile organic P pool into the labile organic P pool ( Zhu et al., 2021 ). In addition, Acidobacteria were favored in acidic soils ( Rousk et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%